Channel-Aware Gradient Descent Bit-Flipping Algorithm for LDPC Codes - Min, Woohong; Yang, Kyeongcheol (IEEE communications letters, 2025)
The gradient descent bit-flipping with momentum (GDBF-w/M) and probabilistic GDBF-w/M (PGDBF-w/M) algorithms significantly improve the decoding performance of the bit-flipping (BF) algorithm. In this letter, we propose a channel-aware GDBF-w/M algorithm which operates deterministically based on the received values from the additive white Gaussian noise (AWGN) channel. Numerical results show that the proposed algorithm does not only mitigate the error-floor phenomenon of the GDBF-w/M algorithm, but it also has better decoding performance than the PGDBF-w/M algorithm without the need for a random number generator. Furthermore, the complexity of the proposed algorithm is slightly higher than that of the GDBF-w/M algorithm.